ChemInform Abstract: Copper—Schiff Base Complex Catalyzed Oxidation of Sulfides with Hydrogen Peroxide. Issue 28 (15th July 2014) - Gogoi, Prasanta; Kalita, Mukul; Bhattacharjee, Tirtha; Barman, Pranjit
Abstract A facile protocol including a copper—Schiff base catalyst allows the selective oxidation of aryl and alkyl sulfides to the corresponding sulfoxides.